A new species of Eudigraphis (Diplopoda, Polyxenida, Polyxenidae) from East China, with embryonic and post-embryonic development observations, and mitogenomic and genetic divergence analyses - Si-Qi Yang; Yun Bu; Nerivania Nunes Godeiro; Yan Gao; Ya-Li Jin (ZooKeys)
Eudigraphis huadongensis Yang & Bu, sp. nov. from east China is described and illustrated. The new species is compared with other congeners in detail and observations about its embryonic and post-embryonic development are provided. The complete mitochondrial genome of the new species is also analyzed, which represents the first published mitogenome of Polyxenida. The genetic divergence between E. huadongensis sp. nov. and its congeners was analyzed using Neighbor-Joining inference based on COI gene sequences. Eudigraphis huadongensis sp. nov. clustered with E. nigricans and E. kinutensis, supporting the morphological identification. The newly assembled mitogenome is 15,206 bp in length and its gene order is unique, possibly representing a pattern among Polyxenida species.